(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Three articles talk about writer O’tkir Hashimov’s novel "Dreams of Past Lives". The commissar’s relationship with the environment, society, conflicts are highlighted. The tragedy of the Soat Ganiyev family is revealed.